THE UNDERSTANDING OF THE STATE CIVIL APPARATUS OF CASCADING IN BENGKULU TENGAH REGENCY - Arief Tangkas Wicaksono; Fachruzzaman (Journal of Economics, Business, and Government Challenges, 2021)
This research aims to determine the understanding of the State Civil Apparatus of cascading in Bengkulu Tengah Regency. This research was conducted at SKPD Central Bengkulu Regency using a qualitative approach. The method uses data in using primary data from in-depth interviews. It supports the distribution of questionnaire data from distributing questionnaires to the Head of Subdivision of Planning, Planning, and Organization in SKPD Bengkulu Tengah Regency as many as 60 sheets. The data validity technique in this study used the triangulation technique of data sources. From the results of the research on the understanding of the State Civil Apparatus towards cascading in the form of the products of the average trend answers and the consequences of in-depth interviews of the State Civil Apparatus in Bengkulu Tengah Regency, understand, apply, and play a role in carrying out cascading, but the process of preparing cascading is still hampered due to the RPJMD in Bengkulu Regency Tengah is still not correct because the RPJMD in Bengkulu Tengah is oriented towards cascading, cascading should be introduced to the RPJMD so that BAPPEDA has difficulty synchronizing the RPJMD and cascading. Based on these results, this research can be used as material for consideration and input for the Regional Government of Bengkulu Tengah Regency.